2022
DOI: 10.1093/heapol/czac070
|View full text |Cite
|
Sign up to set email alerts
|

Under-five mortality in Sierra Leone and possible associated factors: evidence from the 2019 Demographic and Health Survey

Abstract: High under-five mortality rate remains one of the public health challenges, especially in sub-Saharans Africa, accounting for more than half of all global cases. Sierra Leone was and still one of the countries with the highest under-five mortality rate. Using the latest 2019 SLDHS data, we investigated factors associated with under-five mortality in Sierra Leone. A total of 9771 mothers aged 15-49 years in the country were interviewed and included in the analysis. The dependent variable is child status (dead=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 49 publications
1
0
0
Order By: Relevance
“…Children born as multiples had a notably higher probability of not surviving past their fifth birthday than those born singletons. This finding is consistent with earlier studies in Sierra Leone and Ethiopia [ 26 , 45 , 49 ]. Our study exhibited a stronger association (AOR = 1.41) between multiple births and under-five mortality compared to Sierra Leone (AOR = 1.41) [ 26 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Children born as multiples had a notably higher probability of not surviving past their fifth birthday than those born singletons. This finding is consistent with earlier studies in Sierra Leone and Ethiopia [ 26 , 45 , 49 ]. Our study exhibited a stronger association (AOR = 1.41) between multiple births and under-five mortality compared to Sierra Leone (AOR = 1.41) [ 26 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with earlier studies in Sierra Leone and Ethiopia [ 26 , 45 , 49 ]. Our study exhibited a stronger association (AOR = 1.41) between multiple births and under-five mortality compared to Sierra Leone (AOR = 1.41) [ 26 , 45 ]. However, this association was observed to be weaker in Ethiopia (AOR = 4.755) [ 26 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results showed that the top ten important predictors are: wealth index, maternal education, antenatal visits, place of delivery, employment status of the woman, number of children ever born, region, skilled assistance during delivery, frequency of watching television, and birth size. These findings are consistent with the findings of previous studies, which have shown that these factors are all important predictors of U5M [ 43 – 45 ]. The variable importance results support the findings of the conventional logistic regression analysis in this study, which found that wealth index, maternal education, antenatal visits, place of delivery, employment status of the woman, children ever born, region, skilled assistance during delivery, frequency of watching television, and birth size all have a significant impact on U5M in Nigeria.…”
Section: Discussionsupporting
confidence: 93%